2014
DOI: 10.1007/s10120-014-0350-6
|View full text |Cite
|
Sign up to set email alerts
|

Micropapillary component in gastric adenocarcinoma: an aggressive variant associated with poor prognosis

Abstract: Background Adenocarcinomas with a micropapillary component (MPC) have been described as an unusual morphological variant in various organs. However, few reports have described MPCs in gastric carcinomas, and the clinicopathological features of MPC are unclear. Methods Immunohistochemistry was used to detect the expression of epithelial membrane antigen, CK7, CK20, p53, epidermal growth factor receptor, b-catenin, c-erbB-2, and Ki-67. Correlation of the MPC to tumor stage, lymph node metastasis, and lymphovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Carcinomas showing a micropapillary growth pattern were first clearly documented in the breast, but have since been recognised in many other sites, including the lung, bladder, gastrointestinal tract, pancreaticobiliary tract, and salivary gland . Low‐grade serous carcinomas of the ovary also typically have a micropapillary appearance, and this may be a feature, usually focal, of high‐grade serous carcinomas .…”
Section: Introductionmentioning
confidence: 99%
“…Carcinomas showing a micropapillary growth pattern were first clearly documented in the breast, but have since been recognised in many other sites, including the lung, bladder, gastrointestinal tract, pancreaticobiliary tract, and salivary gland . Low‐grade serous carcinomas of the ovary also typically have a micropapillary appearance, and this may be a feature, usually focal, of high‐grade serous carcinomas .…”
Section: Introductionmentioning
confidence: 99%
“…Tumors with type II IMPC behave more aggressively, with higher risks of lymph node metastasis and worse prognosis . The percentage of IMPC component did not significantly affect the metastatic rate of lymph nodes and survival rate . In our case, the tumor contained type II IMPC component.…”
Section: Discussionmentioning
confidence: 41%
“…Two growth patterns have been reported for IMPC: IMPC nests within cystic spaces (type I), and IMPC nests admixed with bands of fibrous connective tissue (type II) . Tumors with type II IMPC behave more aggressively, with higher risks of lymph node metastasis and worse prognosis . The percentage of IMPC component did not significantly affect the metastatic rate of lymph nodes and survival rate .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…26 Since the first identification of micropapillary carcinoma of the stomach, 27 subsequent studies [28][29][30][31][32][33] have demonstrated that gastric cancers (GCs) with an MPC component exhibit aggressive biological behavior, with frequent lymphatic invasion, extensive lymph node metastasis, and lower overall survival. This is similarly observed in other organs.…”
Section: Gastric Adenocarcinoma With a Micropapillary Carcinoma Compomentioning
confidence: 99%